OPTIMALISASI PERAN PEMBIMBING AKADEMIK DI SMA MUHAMMADIYAH PROGRAM KHUSUS KOTTABARAT - Na'imah, Ridha; Ali, Mohamad (PAI RAFAH, 2023)
This Academic advisor, which we usually find at the high school level, it turns out that this program has been implemented at the Senior High School level, namely at SMA Muhammadiyah Kottabarat Special Program. Given the importance of the role of Academic Advisors in supporting student success in study and self-development. Academic advisors have a significant role in helping students achieve optimal academic performance and develop character with integrity. This article discusses the steps that can be taken to maximize the role of academic advisors, including in applying Islamic religious values. The academic advisor is the supervisor of all academic activities that students program in college. In another sense, PA lecturers are lecturers who interact the most with their students. The purpose of this study is to determine the role of Academic Advisors in collaborating with teachers, parents, and students to create a supportive educational environment. This research method uses a descriptive qualitative method with a period of 4 weeks to conduct this research directly by observing and interviewing school parties such as mentor teachers and students of the school. Through an in-depth analysis of the steps that need to be taken in optimizing the role of Academic Advisors, this article provides insight into why this role is so important in producing a quality generation at SMA Muhammadiyah PK Kottabarat.